Mechanical properties of silane treated cenosphere filled polypropylene - Ratiman, Muhammad Rais (2017)
The growing concern about the pollution by fly ash residue resulting from the generation of electricity at thermal power plant, has spurred the development of fly ash for positive uses. However, cenospheres usages are still insignificant compared to production of it. Cenosphere can be utilized more in plastic industry as filler in a polymer plastic. This paper study the effect of the cenosphere as plastic filler to the flexural strength of the composite. This study will give the opportunity to cenosphere to be used in plastic industry. The result from the study shows that the composites’ flexural modulus increases as the weight fraction of cenosphere was added. The silane treatment resulted in considerable improvement in the impact strength and density of the composite.